2010
DOI: 10.2165/11319310-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis Therapy and Cardiovascular Risk Factors

Abstract: Our data show that psoriatic patients present with several lipid profile changes that seem to be related to the severity of the disease and/or the treatment used. Mild psoriasis patients receiving topical treatment presented before starting therapy with a lipid profile similar to controls, whereas those undergoing NB-UVB and PUVA, who had higher PASI scores, presented with several risk factors. Moreover, PUVA therapy seems to interact in a different way with lipids that might result from an interaction of psor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 40 publications
3
56
0
5
Order By: Relevance
“…10 Our results are also supported by the data from Romaní et al, who observed increased systemic levels of LDL cholesterol, non-HDL (high-density lipoprotein) cholesterol and Apo-B in psoriasis patients, levels which were unaffected by phototherapy. 41 Signs of a persistent inflammatory process after UV therapy were also established by Coimbra et al 42 In contrast, UV therapy led to a decrease in IL-22, IL-17, IL-23, IL-8 TNF-α, and VEGF serum levels, 43 suggesting that the skin is the major source of these cytokines in psoriasis. However, the literature is controversial and both we and others have shown a lack of effect by UV therapy on the studied cytokines.…”
Section: T Cells and Langerhans Cells Of The Inflammatory Infiltratementioning
confidence: 78%
“…10 Our results are also supported by the data from Romaní et al, who observed increased systemic levels of LDL cholesterol, non-HDL (high-density lipoprotein) cholesterol and Apo-B in psoriasis patients, levels which were unaffected by phototherapy. 41 Signs of a persistent inflammatory process after UV therapy were also established by Coimbra et al 42 In contrast, UV therapy led to a decrease in IL-22, IL-17, IL-23, IL-8 TNF-α, and VEGF serum levels, 43 suggesting that the skin is the major source of these cytokines in psoriasis. However, the literature is controversial and both we and others have shown a lack of effect by UV therapy on the studied cytokines.…”
Section: T Cells and Langerhans Cells Of The Inflammatory Infiltratementioning
confidence: 78%
“…Cignoline stimulates oxidative stress by enhancing the peroxidation of lipids in keratinocytes and nucleated cells in peripheral blood [75]. Coimbra et al demonstrated no effect of NB-UVB on the inflammatory process or decrease in the risk of atherogenicity: the levels of ox-LDL/LDL, Chol/HDL, CRP and Lp(a) still remained higher than in the control group.…”
Section: Psoriasis Treatment and Lipid Disordersmentioning
confidence: 99%
“…Cygnolina stymuluje stres oksydacyjny poprzez nasilanie peroksydacji lipidów w keratynocytach i komórkach jednojądrzastych krwi obwodowej [75]. Coimbra i wsp.…”
Section: Psoriasis Treatment and Lipid Disordersunclassified
“…Coimbra et al [219] determined a prevalence of cardiovascular risk factors in patients with psoriasis. They demonstrated significantly higher levels of CRP compared to a control group.…”
Section: C-reactive Protein (Crp)mentioning
confidence: 99%